2019
DOI: 10.1103/physrevd.100.025003
|View full text |Cite
|
Sign up to set email alerts
|

Modular Hamiltonian of a chiral fermion on the torus

Abstract: We consider a chiral fermion at non-zero temperature on a circle (i.e., on a torus in the Euclidean formalism) and compute the modular Hamiltonian corresponding to a subregion of the circle. We do this by a very simple procedure based on the method of images, which is presumably generalizable to other situations. Our result is non-local even for a single interval, and even for Neveu-Schwarz boundary conditions. To the best of our knowledge, there are no previous examples of a modular Hamiltonian with this beha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 19 publications
3
39
0
Order By: Relevance
“…The resolvent R 0V Λ is well-known in that case [19], so we can use it to obtain R V via the above equation. In [22] we showed that, in fact, R 0V Λ can be easily computed for generic temperatures, where V Λ is a collection of segments distributed all over the complex plane. In the next section we review the argument in a slightly simplified form.…”
Section: The Methods Of Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The resolvent R 0V Λ is well-known in that case [19], so we can use it to obtain R V via the above equation. In [22] we showed that, in fact, R 0V Λ can be easily computed for generic temperatures, where V Λ is a collection of segments distributed all over the complex plane. In the next section we review the argument in a slightly simplified form.…”
Section: The Methods Of Imagesmentioning
confidence: 99%
“…In a recent paper [22] we computed a new modular Hamiltonian, namely that of a chiral fermion on a circle at non-zero temperature, i.e., on a torus in the Euclidean formalism (see [23] for a related result). The difficulty of the torus is that it cannot be mapped conformally to the plane.…”
Section: Introductionmentioning
confidence: 99%
“…The resolvent for the chiral fermion on the torus was recently obtained in [3] and also in [4]. As direct applications of the resolvent and modular Hamiltonian, we study entanglement entropy, mutual information, threepartite information and relative entropy.…”
Section: Introductionmentioning
confidence: 96%
“…Despite of this, its explicit form is known for the Rindler wedge in any QFT's vacuum state [8], as well as for a spherical entangling surface in CFTs [9] and in time dependent situations after a quantum quench [10]. Some new analytical results were also found recently for free theories and multiple intervals on Minkoski spacetime [11] and the torus [12]. Lastly, we mention that modular Hamiltonians have also been relevant in the context of the AdS=CFT correspondence [13][14][15], in studying the Bekenstein bound [16], the averaged null energy (ANEC) and quantum null energy (QNEC) conditions [17], and emergent gravity [18].…”
Section: Introductionmentioning
confidence: 98%
“…Typical examples of local flows are those produced by modular operators in the vacuum state and for the Rindler wedge [8], or the vacuum of a CFT on a sphere [9] and more recently the single interval case of fermions on a torus [12]. Typical examples of a nonlocal flow is when the region is on the real line and made of disjoint intervals [11] and as well when we study fermions in disjoint intervals on the torus [12]. The modular Hamiltonian K A is a self-adjoint operator that belongs to the algebra of operators, defined on the region A.…”
Section: Introductionmentioning
confidence: 99%